Estudio de prefactibilidad para la instalación de una planta de elaboración de carbón activado a base de cáscara de café - Carrillo Zamora, Jose Manuel (2015)
The present work has the purpose of satisfying a demand generated in the biggest business on the country: mining. The present project will generate economic wellness for a part of the population because it will generate work and economic development. This document presents the economic, social, operative and technological support for the project. The product generated is poorly known on the market but has beneficial applications on minerals processing. The project proposal presents the design of an coffee shell based activated carbon production plant. The minerals processing with the presented product adds value on the final mineral product, generating a competitive advantage in the mining market, that is why we consider that the product will have a big reception and could motivate different mining businesses to add different competitive advantages to their minerals.